Medan City Government Islamic Communication Policy In Resolving The Amal Silaturrahim Mosque Dispute In Medan City - muniruddin, muniruddin; Ridho, Ahmad Rasyid (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Received: Revised: Accepted: Keywords:Policy, Municipal Government, Mosque DisputeThis research aims to find out how the Medan City Government's Islamic communication policy is in resolving the land dispute for the Amal Silaturrahim mosque on Jalan Timah Putih, Medan District, Medan City Area, and what solutions are found after the government's Islamic communication, in this case the level II and sub-district municipal governments and the Affairs Office. Medan District Religion Medan City Area. The research method used is a qualitative method with a descriptive approach. And to obtain data, it was also obtained through interviews, observation and documentation from various aspects in the Medan city government, the Medan area sub-district sub-district office and the cross-sectoral Office of Religious Affairs, as well as an approach to the functional BKM of the Amal Silaturrahim Mosque. The results of the research show that there is an Islamic communication policy in the strategy carried out by the Medan city government in a peaceful effort to resolve the land dispute between the old charity mosque and the land for the new mosque. 1. There is an Islamic communication policy carried out by the government, both between the government and religious functionaries in the management of the old mosque and communication with the management of the new Amal Silaturrahim mosque, as well as government policy in religious matters represented by the Head of the Office of Religious Affairs, 2. Forms of government communication in resolving the dispute over the Amal Silaturrahim mosque Jl. White lead No. 29 in the city of Medan is diagonal communication, namely cross communication, namely communication between section leaders and other section employees, or between one leader and another leader who has different authority